Vertical impulse as a determinant of combination of step length and frequency during sprinting - Nagahara, R.; Takai, Y.; Kanehisa, H.; Fukunaga, T. (International Journal of Sports Medicine, 2018)
This study aimed to clarify the influence of vertical impulse on the magnitude of step length (SL) and frequency (SF) and their ratio during the entire acceleration phase of maximal sprinting. Thirty-nine male soccer players performed 60-m sprints, during which step-to-step ground reaction forces were recorded over a 50-m distance. The mean values of spatiotemporal variables and vertical and anteroposterior impulses for each set of four steps during the acceleration phase until the 28th step were computed to examine relationships among variables in seven sections. When controlling for the influence of running speed, stature and corresponding duration of braking or propulsion, vertical impulses during the propulsive phase at the 1st-4th step section and those during the braking phases in the sections from the 5th-8th to the 25th-28th step were positively correlated with SL and SL/SF ratio and negatively correlated with SF, whereas the anteroposterior impulses were not correlated with SL or SF. In conclusion, the current results demonstrate that vertical impulse during the propulsive phase in the initial acceleration stage and that during the braking phase in the middle and later acceleration stages are the most likely determinants of the combination of SL and SF during sprinting.